Microwave extraction and microencapsulation of polyphenol from phyllanthus niruri - Nguang, Suok Ling (2018)
Phyllanthus Niruri (ver. name: Dukung Anak) contains miscellaneous bioactive compounds which contribute in various medical effects such as antioxidant, anti-inflammatory, anti-cancer and treating Hepatitis-B, jaundice intestinal infection. Extraction is the most common method to obtain the bioactive component from the plant materials. The yield of bioactive component in the extract is dependent on the solvent used, extraction method and condition. In this work, ultrasonic assisted extraction and microwave assisted extraction method were studied as there’s limited work on ultrasonic assisted extraction and microwave assisted extraction were available in the literature. From the finding of this work, it is found that the yield of the bioactive component is highly dependent on solvent polarity used in the extraction, the highest yield of phyllanthin (4.56mg Phy/g DW) was obtained using 20% aqueous Isopropanol whereas the highest yield of quercetin (10.14mg Que/g DW) was obtained by using 20% aqueous ethanol and highest yield of gallic acid (15.44mg GAE/g DW) was obtained by using water. The polarity of solvent enhances the extraction of both hydroxylated and methoxylated compounds from the P. niruri. From the central composite design analysis, microwave assisted extraction at extraction power at 250W, extraction time ranged from 2.47 minutes to 5.72 minutes and ethanol concentration will ranged from 36.58% to 76.31% able to obtain the optimum yield of polyphenol extraction with the desirability of 91.70%. Microwave assisted extraction provided a fast extraction without significantly compromising the extraction yield. Powdered product is often desired due to its longer lifespan, convenient for consumption and easier transportation/ handling. The process of powder making is often carried out in a spray dryer at high temperature (180°C). To minimize degradation of the bioactive compounds during spray drying, microencapsulation method was introduced. WPI and MD encapsulation spray powder had performed a good polyphenol retention from P. niruri. Microencapsulation using mixture of WPI and MD at the ratio 1:9 delivered highest retention of phyllanthin (84.33%), gallic acid (88.93%) and quercetin (88.39%) followed by MD and WPI encapsulation. Microencapsulation using mixture of WPI and MD at ratio 1:9 is suggested as it provides a better preservation of polyphenol during spray drying as opposed to single protein encapsulate of WPI and MD. The results analysis by UPLC illustrates gallic acid and quercetin are more susceptible to thermal degradation than phyllanthin during spray drying. It is recommended to perform a toxicity analysis of P. niruri extract in ACCU accredited lab before it can undergo clinical trial.